IN THE ARTICLE AUTHOR CONSIDER THE ECONOMIC DIRECTION OF LEGAL STATE IN A MARKET ENVIRONMENT - A.S Косжанов (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
In the article author consider the economic direction of legal state in a market environment